2020
DOI: 10.14233/ajchem.2020.22231
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin in Flacourtia inermis Peel: Analysis and Electronic Transition Study

Abstract: This study aimed to determine the anthocyanin content present in Flacourtia inermis peel and its ultraviolet-visible absorption potential as a dye agent. This work focused on developing dye-sensitized materials that require natural eco-friendly dyes which are easily reproducible. The red to purple colour of Flacourtia inermis peel indicates the presence of anthocyanin contents, which were derived from flavonoids. Hence, anthocyanin analysis, UV-vis absorption test and electronic transition study were conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Anthocyanin geometry optimization using density functional theory [34] with Becke 3-parameter Lee-Yang-Parr [35] hybrid functional based on considerations from previous studies that showed good correlation results with experimental results on spectroscopic modeling and chemical properties [36]. The energy calculation from the process of optimizing the geometry of molecular data sets, namely anthocyanin derivatives aims to obtain optimal geometrical conformation [37]. Meanwhile, receptor preparation and reference ligands are carried out using the ff14SB force field with AM1-BCC ligand charge through the Chimera 1.13 package.…”
Section: Modeling and Preparation Of Data Setmentioning
confidence: 99%
“…Anthocyanin geometry optimization using density functional theory [34] with Becke 3-parameter Lee-Yang-Parr [35] hybrid functional based on considerations from previous studies that showed good correlation results with experimental results on spectroscopic modeling and chemical properties [36]. The energy calculation from the process of optimizing the geometry of molecular data sets, namely anthocyanin derivatives aims to obtain optimal geometrical conformation [37]. Meanwhile, receptor preparation and reference ligands are carried out using the ff14SB force field with AM1-BCC ligand charge through the Chimera 1.13 package.…”
Section: Modeling and Preparation Of Data Setmentioning
confidence: 99%